Learning Curves for Laparoscopic Repair of Inguinal Hernia and Communicating Hydrocele in Children - Barroso, Catarina; Etlinger, Péter; Alves, Ana Luísa; Osório, Angélica; Carvalho, José Luís; Lamas-Pinheiro, Ruben; Correia-Pinto, Jorge (Frontiers in Pediatrics, 2017)
Introduction: We analysed the department and surgeon learning curves during implementation of the Percutaneous Internal Ring Suturing (PIRS) technique in our department. Methods: Children proposed for inguinal hernia or communicating hydrocele repair were included (n=607). After mentorship, all surgeons were free to propose open or PIRS repair. From gathered data, we assessed department and surgeon learning curves through cumulative experience focusing in perioperative complications, conversion, ipsilateral recurrence, postoperative complications and metachronous hernia, with benchmarks defined by open repair. Results: Department-centered analysis revealed that perioperative complications, conversion, and ipsilateral recurrence rates were higher in the beginning, reaching the benchmarks when each surgeon performed, at least, 35 laparoscopic repairs. Postoperative complications and metachronous hernia rates were independent from learning curves, with the metachronous hernia rate being significantly lower in PIRS patients. During the program, the percentage of males in those operated by PIRS progressively increased reaching the percentage of males, in our sample, when department operated over 230 cases. Conclusion: Thirty-five laparoscopic cases per surgeon are required for perioperative complications, conversion and ipsilateral recurrence reach the benchmark. The gap between the percentage of males, in those operated by PIRS and in those proposed for surgery, monitors the confidence of the team in the program.